2023
DOI: 10.3389/fnana.2023.1125623
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity of the axon initial segment in rat hippocampal granule cells following high frequency stimulation and LTP induction

Abstract: The axon initial segment (AIS) is the site of action potential initiation and important for the integration of synaptic input. Length and localization of the AIS are dynamic, modulated by afferent activity and contribute to the homeostatic control of neuronal excitability. Synaptopodin is a plasticity-related protein expressed by the majority of telencephalic neurons. It is required for the formation of cisternal organelles within the AIS and an excellent marker to identify these enigmatic organelles at the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Intracellular calcium stores in form of the CO are particularly interesting in this regard [23][24][25] , First, a recent study reported that the number of COs is decreased when rapid AIS plasticity in rat hippocampal DGCs is induced. 39 Here we could show that upon induction of chronic plasticity, there are less COs in the AIS of nonAcD neurons. This correlates with the fewer COs, we found in the AIS of AcD cells.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Intracellular calcium stores in form of the CO are particularly interesting in this regard [23][24][25] , First, a recent study reported that the number of COs is decreased when rapid AIS plasticity in rat hippocampal DGCs is induced. 39 Here we could show that upon induction of chronic plasticity, there are less COs in the AIS of nonAcD neurons. This correlates with the fewer COs, we found in the AIS of AcD cells.…”
Section: Discussionmentioning
confidence: 68%
“…Another direction to explore is the link between the AIS-specific ECM and AIS plasticity. Regardless of our data showing the absence of brevican at the age of neuronal cultures when we performed our experiments (DIV12), it is still possible that the ECM plays a role in older neurons, as AIS is plastic throughout the entire lifespan 28,39,48,49 . Surprisingly, we did not observe any rapid AIS plasticity effect in nonAcD neurons.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations